2010
DOI: 10.1007/s11605-009-1110-5
|View full text |Cite
|
Sign up to set email alerts
|

Subclassification of Stage IV Gastric Cancer (IVa, IVb, and IVc) and Prognostic Significance of Substages

Abstract: Subclassification of stage IV gastric cancer into IVa (T1-2N3M0), IVb (T3N3M0 and T4N1-2M0), and IVc (T4N3M0, TanyNanyM1) may be helpful to predict the outcome and determine the therapeutic strategies for patients with stage IV gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…An et al 14 Ma et al 15 also predicted that subclassification of stage IV gastric cancer into IVA (T1-2N3M0), IVB (T3N3M0 and T4N1-2M0), and IVC (T4N3M0, TanyNanyM1) may be helpful to predict the outcome for patients with stage IV gastric cancer as classified by the 6th edition system. Additionally, Ahn et al determined that survival for pN3 gastric cancer patients after curative gastrectomy was significantly longer in the pN3/M0 group as compared with that of the pN3/M1 group, and advanced T stage was a predictor of poor prognosis for pN3 patients based on 467 cases of gastric cancer patients classified by the 6th edition system.…”
Section: Discussionmentioning
confidence: 99%
“…An et al 14 Ma et al 15 also predicted that subclassification of stage IV gastric cancer into IVA (T1-2N3M0), IVB (T3N3M0 and T4N1-2M0), and IVC (T4N3M0, TanyNanyM1) may be helpful to predict the outcome for patients with stage IV gastric cancer as classified by the 6th edition system. Additionally, Ahn et al determined that survival for pN3 gastric cancer patients after curative gastrectomy was significantly longer in the pN3/M0 group as compared with that of the pN3/M1 group, and advanced T stage was a predictor of poor prognosis for pN3 patients based on 467 cases of gastric cancer patients classified by the 6th edition system.…”
Section: Discussionmentioning
confidence: 99%
“…An et al reported each subgroup of stage IV gastric cancer in the 6th edition system to have different clinical outcomes, and thus subclassification of stage IV gastric cancer into IVA (T1-3N3M0), IVB (T4N1-3M0), and IVM (T[any]N[any]M1) might be useful for more accurate prediction of prognosis 14. Ma et al15 also predicted that subclassification of stage IV gastric cancer into IVA (T1-2N3M0), IVB (T3N3M0 and T4N1-2M0), and IVC (T4N3M0, TanyNanyM1) may be helpful to predict the outcome for patients with stage IV gastric cancer as classified by the 6th edition system. Additionally, Ahn et al determined that survival for pN3 gastric cancer patients after curative gastrectomy was significantly longer in the pN3/M0 group as compared with that of the pN3/M1 group, and advanced T stage was a predictor of poor prognosis for pN3 patients based on 467 cases of gastric cancer patients classified by the 6th edition system 16.…”
Section: Discussionmentioning
confidence: 99%
“…Second, within the same N category, the 5-year OS rates of pT4a patients were similar to those of pT4b patients. In some previous studies, the OS rates of pT4a and pT4b patients were significantly different [21,38]. However, those analyses were not based on the same pN category.…”
Section: Discussionmentioning
confidence: 86%